New record of Thysia wallichii Hope, 1831 (Coleoptera, Cerambycidae) from Arunachal Pradesh, India. - Temjenmongla; Mozhui, L.; Riba, T.; Khongsai, L.S.; Mayi, Y. (ENTOMON, 2026)
The study reports the first confirmed occurrence of Thysia wallichii Hope, 1831 (Coleoptera, Cerambycidae, Lamiinae) from Sangram circle, Kurung Kumey district, Arunachal Pradesh, India. This new locality record extends the known geographical distribution of the species within the state and contributes valuable information to the expanding documentation of cerambycid diversity in the region.